An encouragement to publish powerful studies on innovation in health: A journal preface - Setiyo, Muji; Rahayu, Heni Setyowati Esti; Subrata, Sumarno Adi (Universitas Muhammadiyah Magelang, 2021)
The health manifesto highlighted that studies on innovation flourish when all sides of the knowledge triangle (research, academia, and industry) work in tandem to enhance the quality of care. This opportunity should go much better than implementing theoretical and academic work in universities worldwide. Experts are developing health innovation in higher education to deal with this situation. Therefore, this preface from two experts in the field encourages the importance of publishing studies on innovation in health to reduce health problems and issues in healthcare services in clinical or community practice. Keywords: Innovation; healthcare system; quality of care; clinical practice; community care